Evaluation of The Reproductive Behavior of Male Timor Deer (Cervus timorensis) Agains Weather Changes - Tetty Barunawati Siagian; Nabilla Rachma Putri (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Indonesia has two seasons, namely rainy and dry. During this season, weather changes can occur. These weather changes can affect the reproductive conditions of male deer that are in heat. This study aims to evaluate the reproductive behavior of male Timor deer against weather changes in Ranca Upas Deer Captivity. Observations were made for 14 days on 3 males deer. Observation of male Timor deer reproductive behavior was carried out on the parameters of vocalization, fighting, licking the female, kissing the female genitalia, riding the female, mating, flehmen, wallowing, rubbing the body, and following the female. Observations were made by recording each reproductive activity based on its frequency. Observations were made for 6 hours, namely in the morning and afternoon. Observations were made at a fairly close distance of about 5-10 meters from the deer. Observations were also made of weather, temperature, and humidity. The results of observing the temperature at Ranca Upas Deer Captivity showed that the average temperature in the morning was 18℃ and afternoon 16℃. The average humidity in the morning is 77% and 81% in the afternoon. Observations on the reproductive behavior of male Timor deer showed the effect of weather on sexual reproductive behavior. Cold weather causes mating frequency and sexual activity to increase compared to summer. This condition can be seen from the increase in reproductive activity based on behavior, namely licking the female, kissing the female genitalia, riding the female, mating, flehmen, rubbing the body against the female and following the female